A pilot open‐label phase II trial of rituximab for non‐criteria manifestations of antiphospholipid syndrome1. Issue 2 (28th January 2013) - Erkan, Doruk; Vega, JoAnn; Ramón, Glendalee; Kozora, Elizabeth; Lockshin, Michael D.
Abstract Objective The primary objective of this study was to evaluate the safety of rituximab in antiphospholipid antibody (aPL)–positive patients with non‐criteria manifestations of antiphospholipid syndrome (APS). The secondary objectives were to evaluate the effect of rituximab on the aPL profile and to evaluate the efficacy of rituximab treatment for non‐criteria manifestations of APS. Methods In this 12‐month, phase II pilot study, adult aPL‐positive patients with thrombocytopenia, cardiac valve disease, skin ulcer, aPL nephropathy, and/or cognitive dysfunction received 2 doses of rituximab (1, 000 mg) on days 1 and 15. Antiphospholipid antibody profiles and clinical outcome measures, which were categorized as complete response, partial response, no response, or recurrence, were analyzed at preset time points. Results Two of 19 patients experienced infusion reactions, resulting in early termination. Twelve serious adverse events and 49 nonserious adverse events were recorded. All patients who had positive results of lupus anticoagulant, anticardiolipin, and anti–β2‐glycoprotein I antibody tests at baseline had positive results at 24 weeks and 52 weeks. The numbers of patients with a complete response, a partial response, no response, and recurrence for the clinical outcome measures at 24 weeks were as follows: for thrombocytopenia, 1, 1, 2, and 0, respectively; for cardiac valve disease, 0, 0, 3, and not analyzed, respectively; for skin ulcer, 3, 1, 0, and 1, respectively; for aPL nephropathy, 0, 1, 0, and 0, respectively; and for cognitive dysfunction, 3, 1, 1, and not analyzed, respectively. Conclusion The results of this uncontrolled and nonrandomized pilot study suggest that the safety of rituximab in aPL‐positive patients is consistent with the safety profile of rituximab. Despite causing no substantial change in aPL profiles, rituximab may be effective in controlling some but not all non‐criteria manifestations of APS.